Evaluation of the Effectiveness of a Novel Brain and Vestibular Rehabilitation Treatment Modality in PTSD Patients Who have Suffered Combat-Related Traumatic Brain Injuries - Carrick, Frederick R.; McLellan, Kate; Brock, J. Brandon; Randall, Cagan; Oggero, Elena (Frontiers in Public Health, 2015)
Introduction: Blast-related head injuries are among the most prevalent injuries suffered by military personnel deployed in combat and mild traumatic brain injury (mTBI) or concussion on the battlefield in Iraq/Afghanistan has resulted in its designation as a “signature injury.” Vestibular complaints are the most frequent sequelae of mTBI, and vestibular rehabilitation (VR) has been established as the most important treatment modality for this group of patients. Materials and Methods: We studied the effectiveness of a novel brain and VR treatment post-traumatic stress disorder (PTSD) in subjects who had suffered combat-related traumatic brain injuries in terms of PTSD symptom reduction. The trial was registered as ClinicalTrials.gov Identifier: NCT02003352. (http://clinicaltrials.gov/ct2/show/NCT02003352?term=carrick&rank=6). We analyzed the difference in the Clinician Administered DSM-IV PTSD Scale (CAPS) scores pre- and post-treatment using our subjects as their own matched controls. The study population consisted of 98 combat veterans maintaining an alpha of <0.05 and power of 80%. Results: Prior to treatment, 75 subjects representing 76.53 % of the sample were classified in the 2 most severe categories of PTSD. Forty-one subjects, representing 41.80 % of the total sample, were classified in the extreme category of PTSD and 34 subjects, representing 34.70 % of the total sample, were classified in the severe category of PTSD. After treatment, we observed a large reduction in CAPS severity scores with both statistical and substantive significance. Discussion: Treatment of PTSD as a physical injury rather than a psychiatric disorder is associated with strong statistical and substantive significant outcomes associated with a decrease of PTSD classification. The stigma associated with neuropsychiatric disorders may be lessened when PTSD is treated with brain and VR with a potential decrease in suffering of patients, family, and society.